Pension reform in Korea: the role of policy actors in the dynamics of policymaking - Lee, SY (2016)
This study aims to understand the factors and dynamics that influenced a major social policy change. This is undertaken by unravelling the policymaking processes involved in the largest public pension scheme in Korea, the National Pension System (NPS). Changes to the NPS followed a very different direction to other expansionary welfare developments either in Korea or in similar East Asian welfare systems. This research set out to explain how and why this happened. This is examined via a case study approach with a particular focus on the role of policy actors. This provides an analysis of this single policy change across three time periods, which are characterised by different political and economic regimes: authoritarian rule; democratisation in the midst of a financial crisis; and finally a democracy in recovery from the financial crisis. Data was gained from 44 interviews with the actual policymakers and major policy actors involved, and was complemented by extensive archival data. The findings suggest that, first, although authoritarian governments in Korea may pursue social policy to harness economic development in order to legitimise their non-democratic rule, subtle yet crucial policy competition can still exist among key policy actors. Second, democratisation does not necessarily lead to a dominant view favouring welfare system expansion. Third, new major policy actors – strengthened by a democratic, centre-left government – may not always favour an expansive welfare system. The analysis suggests that, despite the emergence of an increased range and number of policy actors as the democracy matured, there was a marked continuity in policy development in the case of the NPS. Key policy actors pursued a reform in line with liberal economic policy that had been the dominant tendency during the authoritarian era. This suggests that the major mechanism contributing to this continuity was the role of a persistent and powerful epistemic policy community, members of which continued to influence policymaking throughout its development. The conclusion points to how incremental changes in the pension system led to the path dependency of the original policy ideas. We suggest that future research could apply a similar analytical approach to understanding change processes in various policy domains and to other East Asian welfare systems.